2020
DOI: 10.1038/s41598-020-59772-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Extended-spectrum β lactamase- producing E. coli recovered from community-acquired urinary tract infections in Upper Egypt

Abstract: Treatment of community urinary tract infections (UTIs) caused by extended-spectrum β lactamase (ESBL)- producing Escherichia coli (E. coli) is more expensive than treating ESBL-negative opposites. Evaluation of the prevalence of ESBL-production among urinary E. coli isolates is crucial due to its great impact on the choice of proper antimicrobials. Accordingly, the aim of this work was to detect and characterize ESBL-producing E. coli isolated from outpatients with signs of UTIs in Upper Egypt. Urinary E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
51
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 43 publications
27
51
2
Order By: Relevance
“…In addition, one ESBL-producing E. coli isolate is susceptible to ampicillin (Table 3) and this isolate was negative to all ESBL genes tested in this study. This phenomenon agrees with previous studies that were conducted in ESBL-producing E. coli from various clinical samples [26][27][28][29]. However, it is still unclear about genetics underlying ESBL production in this ampicillin-resistant ESBL producing strain.…”
Section: Resultssupporting
confidence: 92%
“…In addition, one ESBL-producing E. coli isolate is susceptible to ampicillin (Table 3) and this isolate was negative to all ESBL genes tested in this study. This phenomenon agrees with previous studies that were conducted in ESBL-producing E. coli from various clinical samples [26][27][28][29]. However, it is still unclear about genetics underlying ESBL production in this ampicillin-resistant ESBL producing strain.…”
Section: Resultssupporting
confidence: 92%
“…This difference may be attributed to the use of molecular technique in our study as against phenotypic detection in theirs, since the latter is known to be less sensitive compared to the former. Our result is very similar to the 33 and 33.5% earlier reported from Saudi Arabia and Egypt by Abdulaziz et al (2018) and Hassuna et al (2020), respectively. Previous workers (Saravanan et al, 2018;Abdulaziz et al, 2018;Hassuna et al, 2020), have also reported higher prevalence of bla-CTX gene in the middle-East and Africa, but our study showed the bla-TEM gene dominating over the bla-CTX gene with the bla-SHV being completely absent.…”
Section: Discussionsupporting
confidence: 93%
“…Available literature has demonstrated a risen prevalence of multidrug resistant ESBL-producing E. coli globally (Hassuna et al, 2020;Abdulaziz et al, 2018;Falgenhauer et al, 2019). Our study is predicated on the paucity of data from the West African sub-region on ESBLs resistant genes in HIV-infected individuals.…”
Section: Introductionmentioning
confidence: 89%
“…Escherichia coli producing narrow and extended spectrum beta-lactamases (ESBL) are continuously becoming a public health problem worldwide [3,4]. ESBL are plasmid-mediated βlactamase enzyme recognized for their remarkable ability to hydrolyse, penicillin, 3 rd and 4 th generation cephalosporins and monobactams except for carbapenem and cephamycin [5]. These enzymes emerged from blaTEM-1, blaTEM-2, and blaSHV a narrow-spectrum parent.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, blaCTX-M, a new class of ESBL genes appeared have gained global traction, because of the burden it placed on environment health. Amino acid sequence analysis of CTX-M variant grouped these enzymes into five distinct clusters including CTX-M-1, CTX-M-2, CTX-M-8, CTX-M-9, and CTX-M-25 [4,5]. The success of the genes in the ecosystem may likely be associated with the spread of bacterial strains carrying ESBL genes and horizontal transfer of these genes on transmissible plasmids [6][7][8].…”
Section: Introductionmentioning
confidence: 99%